Learning and enjoy intermediate statistics : the easy way : textbook-workbook - Uriarte, Gabriel G. (Quezon City : Wiseman's Book Trading, 2024)
Learn and Enjoy Intermediate Statistics the Easy Way Volume 2 is the answer to the desire of students to learn statistics the easy way and apply what they have learned in their daily activities and in the future in the field of statistics. This book has been designed to help them understand the different concepts and theories in statistics since it contains topics relevant to the study of statistics principles which serves as guide in the application of aforesaid concepts. Each chapter starts with a table containing the Topic/s, Learning Outcomes identified as cognitive, affective and psychomotor, Guide Questions for Group Oral Interaction, Suggested Activities for students and teachers, and Assessment Modalities. This serves as a guide for them on what to achieve in the study of every topic and discussion in the whole chapter. Each chapter is motivated by a question that needs to be answered: The statistical analysis flows naturally from the questions. The Discussions in every chapter are made easy and simple for clearer and better understanding of the different statistics concepts, theories, and principles, which focus more on application, and valuing. The discussions attempt to demonstrate the logic of the analyst and emphasize the interactive and literative nature of the task. This book aims to show the students by example that statistical analysis clarifies and throws light on a complex situation. It enables one to draw useful conclusions. Besides the conclusions, much is learned about the problem during the analysis.
Includes bibliographical references.
Keywords: Statistics